Time Management Profile of 7th Grade Student at SMP Negeri 2 Semarang - Belvaza Feilasifa; Dini Rakhmawati; Ani Prihatin Joediati (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
English: The problem of student’s time management is still found to be the background for this research, This research aims to find out a picture of time management for class VII students at SMP Negeri 2 Semarang. This research applies a quantitative approach and descriptive study methodology. The total sample for this research was 172 class VII students with the sample collection technique using simple random sampling techniques. The results of research and data analysis show that the time management of class VII students at SMP Negeri 2 Semarang is on average in the medium category, 72 students (42.20%), there are students who have a high level of time management namely 40 students (21, 60%), and 60 students (36.20%) in the low management deficiency category. The findings of this study highlight the important role of guidance and counseling teachers in fostering positive behavior among students at school, which is crucial for the optimal development of their social skills and the improvement of their time management abilities. Indonesia: Masih ditemukan masalah manajemen waktu peserta didik jadi latar belakang dari penelitian ini, penelitian ini bertujuan untuk mengetahui gambaran manajemen waktu pada peserta didik kelas VII di SMP Negeri 2 Semarang. Penelitian ini menerapkan pendekatan kuantitatif dan metodologi studi deskriptif. Jumlah sampel penelitian ini ialah 172 siswa kelas VII dengan teknik penghimpunan sampel menerapkan teknik simple random sampling. Hasil penelitian dan analisis data menunjukkan manajemen waktu peserta didik kelas VII di SMP Negeri 2 Semarang rata-rata berada di kategori sedang 72 peserta didik (42,20%), ada peserta didik yang mempunyai taraf manajemen waktu tinggi sejumlah 40 peserta didik (21,60%), dan 60 peserta didik (36,20%) dengan kategori rendah manajemen waktunya. Hasil penelitian ini dapat memberikan peran guru BK dalam mengembangkan perilaku yang baik pada peserta didik di sekolah agar proses perkembangan sosial peserta didik dapat berkembang dengan optimal, agar peserta didik memiliki keterampilan manajemen waktu yang baik.